An ecological momentary assessment study to investigate individuals' reactions to perceived social exclusion. (January 2023) - Pancani, Luca; Waldeck, Daniel; Tyndall, Ian; Riva, Paolo
Abstract: Most psychological research on social exclusion mainly focused on maximizing internal validity (e.g., controlling for confounding variables). However, maximizing external validity to produce generalizable knowledge about real-world experiences becomes increasingly essential. In the present study ( N  = 89), we adopted an ecological momentary assessment (EMA) design to track exclusionary experiences and their impact on psychological distress over 15 consecutive days. We tested the mediating effects of positive and negative emotions on the link between daily exclusionary experiences and psychological distress, examining the moderating role of experiential avoidance (EA). Results confirmed a large effect of social exclusion on distress mediated by positive and negative emotions. However, EA did not moderate the exclusion-distress link but was, unexpectedly, found to moderate the exclusion-positive emotions relationship. Specifically, this relationship was stronger for low (vs. high) levels of EA, indicating that adopting EA in response to perceived exclusion may provide a protective function from blunted positive emotions. The present study suggests the usefulness of investigating the occurrence and reactions to the daily experiences of social exclusion, going beyond the sole reliance on experimental manipulations, especially to explore the role of individual differences in working towards a more integrated theoretical model of exclusion. Highlights: The literature on social exclusion outcomes is robust but lacks external validity. Through EMA design, we investigated the consequences of daily social exclusion. Positive and negative emotions fully mediate the exclusion-distress link. Experiential avoidance buffers exclusion effects by maintaining positive emotions.